International Search and Extradition of Fugitives - STOJANOVSKI, Sasho; STEFANOVA, Biljana (Journal of Legal Studies, 2014)
Modern crime with all its singularities, growth dynamics, scope, structure, new and more severe manner of execution, certainly represents an increased threat to the vital interests of the individual, community and safety. Crime is no longer a problem only for one country or region, it becomes global. Crime and criminals are no longer territorial or geographically limited within certain countries, it's transnational. Using the benefits of opening the previously closed borders and the abolition of border controls, development of information and communication technology, transportation, transcontinental mobility, changes in social, political and economic systems in the world, crime and criminals often rapidly change place of residence after committing the crime. Having in mind the above mentioned, dealing with crime and its perpetrators requires modern and serious approach and cooperation of international enforcement of laws and appropriate and effective instruments for searching, locating the perpetrators of crimes, arrest and their extradition. The paper will analyze existing instruments that are used from the bodies of criminal law enforcement to determine their advantages and disadvantages in practical application, and duration of proceedings in terms of simplification, faster and effective implementation. We think that this way it will give its contribution to overcoming the problems that are caused by perpetrators of particular crimes especially fugitives from the law.